Analysis of Public Policy Regarding Hotel Accommodation for Sustainable Tourism in Bali - Ni Made Hintya Mahayani (Westscience Press, 2026)
The rapid development of tourism in Bali has encouraged the growth of significant hotel accommodation development. However, this development raises various problems, one of which is the practice of privatizing coastal border areas by hotel accommodation providers. This study aims to analyze the analysis of public policy regarding hotel accommodation for the benefit of tourism in Bali and examine the analysis of hotel accommodation policy towards the privatized coastal border area, with a case study on Puri Santrian A Beach Resort and Spa in the Sanur Beach Area, Denpasar. This study uses a descriptive qualitative research method used to analyze and describe the analysis of public policy regarding hotel accommodation for tourism purposes in Bali, especially related to the practice of privatization of coastal border areas. Research shows that the analysis of public policy regarding hotel accommodation has not been optimal. This is due to four main factors, namely: (1) communication that is not well established between the Governor as a policy maker and the Regent as the policy implementer, thus causing an overlap of authority; (2) limited resources, both in terms of quantity and quality of local government apparatus; (3) the disposition or willingness of policy implementers is weak because it is faced with their respective interests in increasing regional revenue; and (4) ineffective bureaucratic structures due to different understandings among local governments in understanding the substance and output of policies. Although the government has issued various regulations related to the protection of coastal borders, there is no policy that specifically regulates the practice of privatization of coastal borders. The government's inconsistency in policy enforcement is one of the main factors why the practice of privatization of coastal borders continues to this day. This study concludes that good synergy and communication between provincial and district/city governments are needed in the analysis of tourism policies, increasing the capacity of apparatus resources, and enforcing firm and consistent policies on the practice of privatization of coastal borders to realize sustainable tourism development and community welfare.